2003
DOI: 10.1161/01.cir.0000101923.54751.77
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Transcription Factor 1 Protects Cardiomyocytes From Ischemia/Reperfusion Injury

Abstract: Background-Because cardiomyocyte death causes heart failure, it is important to find the molecules that protect cardiomyocytes from death. The death trap is a useful method to identify cell-protective genes. Methods and Results-In this study, we isolated the heat shock transcription factor 1 (HSF1) as a protective molecule by the death trap method. Cell death induced by hydrogen peroxide was prevented by overexpression of HSF1 in COS7 cells. Thermal preconditioning at 42°C for 60 minutes activated HSF1, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 36 publications
5
40
0
Order By: Relevance
“…Recent studies showed the important role of the PI3K-Akt signaling pathway in survival of cardiomyocytes as well as protection against myocardial I/R injury in mice (2,61,71). The antiapoptotic effect of Akt is mediated by direct phosphorylation and inactivation of proapoptotic proteins, including caspase-9, an upstream activator of caspase-3 (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed the important role of the PI3K-Akt signaling pathway in survival of cardiomyocytes as well as protection against myocardial I/R injury in mice (2,61,71). The antiapoptotic effect of Akt is mediated by direct phosphorylation and inactivation of proapoptotic proteins, including caspase-9, an upstream activator of caspase-3 (18).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrated the activation of ERK1/2 after reperfusion, which is cardioprotective (23,29,41,68). Phosphatidylinositol 3-kinase (PI3K)-Akt signaling is an important mediator of cell survival and promotes survival of cardiomyocytes in vitro and in vivo (2,61,71). In addition, it protects against acute I/R injury in the mouse heart (2,71).…”
mentioning
confidence: 99%
“…16 By inducing Hsps, heat shock can prevent apoptosis in cardiomyocytes. 17,18 Also, hyperthermia protected mice from tumor necrosis factor 19 and gamma radiation. 20 Yet, heat shock cannot be safely used in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Akt promotes the survival of cardiomyocytes in vitro in addition to protection against acute I/Rinduced injury in the mouse heart (4,5). Similarly, our recent study showed that kallikrein gene delivery protects against cerebral ischemia injury and apoptosis along with activation of Akt signaling (6).…”
mentioning
confidence: 99%